Polymer brain-nanotherapeutics for multipronged inhibition of microglial α-synuclein aggregation, activation, and neurotoxicity. (December 2016) - Bennett, Neal K.; Chmielowski, Rebecca; Abdelhamid, Dalia S.; Faig, Jonathan J.; Francis, Nicola; Baum, Jean; Pang, Zhiping P.; Uhrich, Kathryn E.; Moghe, Prabhas V.
Abstract: Neuroinflammation, a common neuropathologic feature of neurodegenerative disorders including Parkinson disease (PD), is frequently exacerbated by microglial activation. The extracellular protein α-synuclein (ASYN), whose aggregation is characteristic of PD, remains a key therapeutic target, but the control of synuclein trafficking and aggregation within microglia has been challenging. First, we established that microglial internalization of monomeric ASYN was mediated by scavenger receptors (SR), CD36 and SRA1, and was rapidly accompanied by the formation of ASYN oligomers. Next, we designed a nanotechnology approach to regulate SR-mediated intracellular ASYN trafficking within microglia. We synthesized mucic acid-derivatized sugar-based amphiphilic molecules (AM) with optimal stereochemistry, rigidity, and charge for enhanced dual binding affinity to SRs and fabricated serum-stable nanoparticles via flash nanoprecipitation comprising hydrophobe cores and amphiphile shells. Treatment of microglia with AM nanoparticles decreased monomeric ASYN internalization and intracellular ASYN oligomer formation. We then engineered composite deactivating NPs with dual character, namely shell-based SR-binding amphiphiles, and core-based antioxidant poly (ferrulic acid), to investigate concerted inhibition of oxidative activation. In ASYN-challenged microglia treated with NPs, we observed decreased ASYN-mediated acute microglial activation and diminished microglial neurotoxicity caused by exposure to aggregated ASYN. When the composite NPs were administered in vivo within the substantia nigra of fibrillar ASYN-challenged wild type mice, there was marked attenuation of activated microglia. Overall, SR-targeting AM nanotechnology represents a novel paradigm in alleviating microglial activation in the context of synucleinopathies like PD and other neurodegenerative diseases. Graphical abstract: